The Relationship Between Parenting Patterns And The Development Of Children 1 Year Old: Hubungan Pola Asuh Orang Tua dengan Perkembangan Anak Usia 1 Tahun - Waode Ikrawati; Wiwin winarsih; Asni Asni (Napande: Jurnal Bidan, 2023)
The way parents educate and raise children is influenced by several factors including culture, religion, habits and personality of parents. An active role in child development is needed, especially when a child is 1 year old. This study aims to determine the relationship between parenting style and the development of children aged 1 year. This type of research is analytic correlation with a cross sectional approach. From the results of the study, it was found that the majority (52.5%) of respondents who implemented autorative parenting styles fully (100%) experienced appropriate developments and nearly half (37.5%) of the total respondents adopted deviant parenting patterns, almost half experienced developments. appropriate and most (67%) experienced the development of deviations. From this study it can be seen that most of the respondents applying authorative parenting experienced appropriate developments. Parents need to know and understand in applying parenting styles that are appropriate to the child's developmental stage.